Oncolytic herpes simplex virus type 1 (HSV‐1) in combination with lenalidomide for plasma cell neoplasms. (20th November 2020) - Oku, Maki; Ishino, Ryo; Uchida, Shumpei; Imataki, Osamu; Sugimoto, Naoshi; Todo, Tomoki; Kadowaki, Norimitsu
Abstract: Oncolytic viruses exert an anti‐tumour effect through two mechanisms: direct oncolytic and indirect immune‐mediated mechanisms. Although oncolytic herpes simplex virus type 1 (HSV‐1) has been approved for melanoma treatment and is being examined for its applicability to a broad spectrum of malignancies, it is not known whether it has an anti‐myeloma effect. In the present study, we show that the third‐generation oncolytic HSV‐1, T‐01, had a direct oncolytic effect on five of six human myeloma cell lines in vitro . The anti‐tumour effect was enhanced in the presence of peripheral blood mononuclear cells (PBMCs) from healthy individuals and, to a lesser extent, from patients with myeloma. The enhancing effect of PBMCs was abrogated by blocking type I interferons (IFNs) or by depleting plasmacytoid dendritic cells (pDCs) or natural killer (NK) cells, suggesting that pDC‐derived type I IFNs and NK cells dominated the anti‐tumour effect. Furthermore, the combination of T‐01 and lenalidomide exhibited enhanced cytotoxicity, and the triple combination of T‐01, lenalidomide and IFN‐α had a maximal effect. These data indicate that oncolytic HSV‐1 represents a viable therapy for plasma cell neoplasms through direct oncolysis and immune activation governed by pDCs and NK cells. Lenalidomide is likely to augment the anti‐myeloma effect of HSV‐1.